ð˜—ð˜™ð˜ˆð˜›ð˜ ð˜“ð˜Œð˜•ð˜Šð˜ð˜œð˜š ð˜‰ð˜™ð˜ˆð˜Šð˜ð˜ ð˜œð˜™ð˜œð˜š PARASITA FUMO NA BAHIA - Zem, Antonio Carlos; Monteiro, Ailton Rocha (REVISTA DE AGRICULTURA, 2020)
ð˜—ð˜™ð˜ˆð˜›ð˜ ð˜“ð˜Œð˜•ð˜Šð˜ð˜œð˜š ð˜‰ð˜™ð˜ˆð˜Šð˜ð˜ ð˜œð˜™ð˜œð˜š PARASITA FUMO NA BAHIA